The influence of task and interpersonal interdependence on cooperative behavior and its neural mechanisms - Zijun Yin; Bin Xuan; Chengchi Liu; Jingchao Yi; Xiaoyan Zheng; Mingming Zhang (npj Science of Learning)
Abstract Previous studies have insufficiently explored the influence of task and interpersonal interdependence on synchronous cooperation behavior. To address this gap, this study utilized fNIRS hyperscanning technique to investigate the behavioral and neural mechanisms within both friend and stranger dyads engaging in various levels of interdependent cooperation tasks. Our findings revealed that high interdependent cooperation task can improve the behavioral performance of both friend and stranger dyads, enhancing the intra-brain functional connectivity (FC) of right dorsolateral prefrontal cortex (DLPFC.R) and right supramarginal gyrus (SMG.R) in stranger dyads, as well as the inter-brain synchrony (IBS) of SMG.R. Additionally, high interdependent interpersonal relationship can strengthen the intra-brain FC of DLPFC.R and SMG.R, as well as the IBS of SMG.R, during low interdependent cooperation task. These insights underscore the critical importance of both task and interpersonal interdependences in shaping cooperative behavior and neural synchrony.